Programa Moenli para mejorar la motricidad gruesa de estudiantes de 2 años del centro educativo Rafael Narváez Cadenillas, Trujillo-2018. - Cárdenas Aguilar, Karla Dennise_x000D_ Garcia Alberca,Alondra Analí (2019)
The purpose of this research work is to demonstrate that the application of the MOENLI program improves gross motor skills through innovative activities under the approach of Emmi Pikler._x000D_ The present investigation was based on the little development of gross motor skills presented by the students of 2 years of C.E. Rafael Narváez Cadenillas from the city of Trujillo in 2018, which was observed at the time when the teacher carried out her psychomotor activities_x000D_ The research is applicable and we use the pre-experimental design with a single group, with pretest and posttest. This research was conducted on a sample of 10 2-year-old students, with whom the MOENLI program was applied, which lasted for 2 months._x000D_ When the evaluation instrument was applied to measure the level of motor skills in 2-year-old students, a score of 90% was obtained in the pretest, evidencing a low development of gross motor skills. But after applying the MOENLI program, the score obtained in the post-test was 90%, which showed an increase in their level of motor skills.